2020
DOI: 10.1111/bjh.16669
|View full text |Cite
|
Sign up to set email alerts
|

De‐Iron: a phase 2 trial of the activity and safety of Deferasirox administered at early iron loading in patients with transfusion‐dependent myelodysplastic syndromes

Abstract: Prognostic factors and life expectancy in myelodysplastic syndromes classified according to WHO criteria: a basis for clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Patients receiving regular blood transfusions will inevitably develop iron overload. Although evidence is accumulating for the benefit of iron chelation therapy in MDS patients with transfusion‐related iron overload, 54 there is a paucity of data in AA. The 1‐year Evaluation of Patients' Iron Chelation with Exjade study 55 showed chelation with deferasirox was safe and could reduce the ferritin level.…”
Section: Supportive Carementioning
confidence: 99%
“…Patients receiving regular blood transfusions will inevitably develop iron overload. Although evidence is accumulating for the benefit of iron chelation therapy in MDS patients with transfusion‐related iron overload, 54 there is a paucity of data in AA. The 1‐year Evaluation of Patients' Iron Chelation with Exjade study 55 showed chelation with deferasirox was safe and could reduce the ferritin level.…”
Section: Supportive Carementioning
confidence: 99%